Cutting Edge: Physiologic Attenuation of Proinflammatory Transcription by the Gs Protein-Coupled A2A Adenosine Receptor In Vivo - Dmitriy Lukashev; Akio Ohta; Sergey Apasov; Jiang‐Fan Chen; Michail V. Sitkovsky (2004)
The A2A adenosine receptor plays a critical role in the physiologic immunosuppressive pathway that protects normal tissues from excessive collateral damage by overactive immune cells and their proinflammatory cytokines. In this study, we examine and clarify the mechanism of tissue protection by extracellular adenosine using A2AR-deficient mice and show that the A2AR inhibits TLR-induced transcription of proinflammatory cytokines in vivo. The observed increase in proinflammatory cytokines mRNA in A2AR-deficient mice was associated with enhanced activity of the NF-kappaB transcription factor. These observations provide the genetic in vivo evidence for attenuation of proinflammatory transcriptional activity of NF-kappaB by a "metabokine" adenosine and point to the need to re-evaluate the regulation of other transcription factors in hypoxic and adenosine-rich microenvironments of inflamed normal tissues and solid tumors.